Kajian Kerentanan Tsunami Menggunakan Metode Sistem Informasi Geografi di Kabupaten Bantul, Daerah Istimewa Yogyakarta - Mardiyanto, Bangun; Rochaddi, Baskoro; Helmi, Muhammad (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Indonesian archipelago directly opposite to the subduction zone between the Indo-Australian plate with the Eurasian plate. Based on plate movements, earthquakes are common in the Indian Ocean. As a result, the southern part of Java Island is very prone to earthquakes. If earthquakes occur beneath the sea and vertical fracture occurs, it will cause a tsunami. The purpose of this research is to create a map of vulnerability to tsunamis in the region peisir Bantul, Yogyakarta using Geographic Information Systems technology (GIS) and identify any areas that are highly vulnerable The research was conducted in March 2012 until August 2012. The method of analysis in this research is qualitative and quantitative. The methodology used in this study include data gathering both primary and secondary data include satellite imagery, DEM, scale 1:25,000 Topographic maps, demographic data, seismic positioning data, bathymetry data, and earthquake data fault. Processing parameters data that represent each variable vulnerability, ie environmental vulnerability, physical, social and economic was weight and then given a vulnerability score of each variable, vulnerability areas data processing to tsunami to get the vulnerability of the region to the tsunami map and field surveys. Villages in coastal areas that have a high level of tsunami vulnerability is Poncosari Village, Gadingsari Village, Gadingharjo Village, Srigading Village, Tirtoharo Village, Donotirto Village and Parangtritis village. Land use in Bantul related to human activities that weredamage threatened by the tsunami are residential, gardens, fields, ponds, moor and forest.